O SENAI e a inserção do jovem aprendiz no mercado de trabalho formal - Lima, Sólon Nogueira de (2009)
This study investigates the impact on the contribution of industrial learning for employability among young learners. The Government, through the Law of the Apprentice (10,097 / 2000) has been implementing policies to generate employment for youth 14 to 24 years in colleges, in order to foster job creation among the younger age group, working to achieve social inclusion, self-esteem and ensure development opportunities for this segment of society. To assess the impact of participation in the courses of SENAI will be utilized the methodology of Propensity Score Matching and the result shows positive for those who underwent industrial training courses, increasing the probability of an individual entering the labor market.